The Relationship between Rate and Volume of Intravenous Fluid Administration and Kidney Outcomes after Angiography. Issue 10 (October 2022) - Soomro, Qandeel H.; Anand, Sonia T.; Weisbord, Steven D.; Gallagher, Martin P.; Ferguson, Ryan E.; Palevsky, Paul M.; Bhatt, Deepak L.; Parikh, Chirag R.; Kaufman, James S.
Visual Abstract: Abstract : Background and objectives: Contrast-associated AKI may result in higher morbidity and mortality. Intravenous fluid administration remains the mainstay for prevention. There is a lack of consensus on the optimal administration strategy. We studied the association of periprocedure fluid administration with contrast-associated AKI, defined as an increase in serum creatinine of at least 25% or 0.5 mg/dl from baseline at 3–5 days after angiography, and 90-day need for dialysis, death, or a 50% increase in serum creatinine. Design, setting, participants, & measurements: We conducted a secondary analysis of 4671 PRESERVE participants who underwent angiographic procedures. Although fluid type was randomized, strategy of administration was at the discretion of the clinician. We divided the study cohort into quartiles by total fluid volume. We performed multivariable logistic regression, adjusting for clinically important covariates. We tested for the interaction between fluid volume and duration of fluid administration, categorized as <6 or ≥6 hours. Results: The mean (SD) age was 70 (8) years, 94% of participants were male, and median (interquartile range) eGFR was 60 (41–60) ml/min per 1.73 m 2 . The range of fluid administered was 89–882 ml in quartile 1 and 1258–2790 ml in quartile 4. Compared with the highest quartile (quartile 4) of fluid volume, we found a significantly higher risk of the primary outcome in quartile 1 (adjusted odds ratio, 1.58; 95% confidence interval, 1.06 to 2.38) but not in quartiles 2 and 3 compared with quartile 4. There was no difference in the incidence of contrast-associated AKI across the quartiles. The interaction between volume and duration was not significant for any of the outcomes. Conclusions: We found that administration of a total volume of 1000 ml, starting at least 1 hour before contrast injection and continuing postcontrast for a total of 6 hours, is associated with a similar risk of adverse outcomes as larger volumes of intravenous fluids administered for periods >6 hours. Mean fluid volumes <964 ml may be associated with a higher risk for the primary outcome, although residual confounding cannot be excluded.